Values and Violence Endorsement Among College Students in Turkey - Veysel Bozkurt; Hakan Gülerce (İnsan & Toplum)
This study examines the impact of values on approval of violence. Data was collected from university students with a stratified random sample. The results showed that violence endorsement has a statistically significant positive correlation with tradition, stimulation and power values, whereas universalism, security, conformity, and benevolence values have negative correlations with violence endorsement. The approval of violence did not have any significant relationship with self-direction, hedonism and achievement values. The effects of violence exposure and gender on violence approval were also examined and both were determined to be highly influential. However, the main theme of the research was the effect of values on violence endorsement. Multiple regression analysis showed that the most important predictor values are universalism, stimulation, tradition and power values. The absolute antidotes to violence were the universal values of equality, wisdom, peace, tolerance and nature conservation etc. Greater importance given to these universal values in education policies could help to reduce the endorsement of violence.